The Influence of Satisfaction on Quality Dimensions Services Financing Mudharabah to Customers Loyalty of Shariah Bank - Romi Iskandar; Winda Afriyenis; Nila Pratiwi; Anita Ade Rahma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2016)
This research aims to understand the influence of satisfaction on the quality of services financing Mudharabah to loyalty the customers about the manner of Shariah bank. The Population of this research is customers of Mudharabah financing of Shariah bank in the Padang city, West Sumatera, Indonesia with the sample is 126 people. Data analysis technique uses statistics descriptive the frequency and the path analysis. The results show that 5 external variables namely satisfaction on the quality of services tangible dimension empathy, reliability, responsiveness, assurance influential significantly to loyalty to the bank customers shariah in the Padang city. Contributing on each satisfaction on the quality of services tangible dimension (11.81 %), empathy (15.55 %), reliability (23.48 %), responsiveness (22.60 %), and assurance (21.22 %) were recommended to bank about the manner of shariah bank in the city the Padang. They helps to raise and improving the quality of services financing Mudharabah particularly regarding to the from the parking lot, the number of ATM machine, concern at a venture customers, the accuracy of the schedule of distribution financing, order and long a queue, smooth bank-in and cash withdrawal, speed service and facilities for customers in conveyed any complaints to bank about the manner of Shariah bank.